FACTORS INFLUENCING CAPITAL STRUCTURE IN THE FIRST YEAR OF THE COVID-19 PANDEMIC - Asto Sunu Subroto (Bajang Institute, 2024)
Several previous studies on the factors that influence the capital structure of manufacturing companies on the Indonesia Stock Exchange show that the determination of capital structure is proven to be significantly influenced by several factors. The Covid-19 pandemic has had a very significant impact on the Indonesian economy, starting from changes in world supply chains to a decline in foreign investment into Indonesia. Factors that affect a manufacturing company in determining its capital structure in the first year of the Covid-19 pandemic could be very different from when the Covid-19 pandemic had not yet hit Indonesia. Initially, the sample used in this study covered 193 manufacturing companies, but later 23 companies were excluded because of data outliers. The independent variables in this research are profitability, liquidity, asset structure and company size. Meanwhile, the dependent variable is capital structure. The collected data will be analyzed using multiple regression analysis at a significance level of 5%. Profitability has a significant negative effect on capital structure. While partially, firm size and liquidity has a negative effect on capital structure, but it is not significant. Asset structure has a positive effect on capital structure, but it is not significant. Simultaneously, profitability, liquidity, asset structure and company size have a significant effect on capital structure